PVDF dispersion glue and preparation method thereof
The PVDF dispersion prepared by the two-stage polymerization method solves the problem of insufficient bonding strength of water-based binders in lithium batteries, improves the bonding strength and permeability between the separator and the electrode, reduces the risk of internal short circuit, and promotes the improvement of lithium battery safety and performance.
Patent Information
- Application Number
- CN202511457969.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-13
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-10-13
AI Technical Summary
Existing water-based binders struggle to balance high peel strength and low permeability, resulting in insufficient bonding strength between the lithium battery separator and the electrode, increasing the risk of internal short circuits and battery performance degradation.
PVDF dispersion was prepared using a two-stage polymerization method, combining emulsion polymerization and solution polymerization. This method utilizes the strong interaction between acrylic monomers and PVDF to improve the bonding strength between the diaphragm and the electrode and reduce the impact of air permeability.
It significantly improves the dry and wet peel strength between the separator and the electrode, reduces the risk of internal short circuit, enhances battery cycle performance and safety, while maintaining the permeability of the separator, making it suitable for long-life lithium batteries.
Smart Images

Figure CN121293429B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy technology, and in particular to a PVDF dispersion and its preparation method. Background Technology
[0002] With the rapid development of new energy vehicles and the energy storage industry, the demand for energy density and cycle life of lithium-ion batteries continues to increase. As a key component of the battery, the stability of the separator's interface with the electrodes directly affects battery performance. Traditional polyolefin separators (PE / PP) have weak interactions with the positive and negative electrodes due to their surface chemical inertness, making them prone to relative displacement during charging and discharging, increasing the risk of internal short circuits. Currently, the industry commonly uses modified PVDF (polyvinylidene fluoride) coatings to pretreat the separators, utilizing their excellent adhesion and electrolyte affinity to improve interface stability. However, the current approach involves coating the separator with a layer of PVDF material and then bonding the separator to the electrode during battery assembly via hot-pressing. This reduces the risk of slippage between the separator and the electrode, improving safety. However, existing technologies have significant bottlenecks: while solvent-based PVDF methods offer high hot-pressing peel strength, the coating process relies on toxic organic solvents such as NMP (N-methylpyrrolidone), which not only pollutes the environment but also increases costs (accounting for over 35% of coating costs). Furthermore, conventional water-based binders (such as acrylic emulsions) have poor compatibility with PVDF, resulting in low bonding strength between the coating and the electrode. Therefore, developing a green process route combining water-based binders with PVDF has become an urgent industry need.
[0003] Commonly used water-based binders are represented by LA133, a submicron-sized, large-particle-size acrylic emulsion with good permeability and minimal impact on battery internal resistance. However, its adhesion to PVDF and separator substrates is weak, resulting in low hot-press peel strength, especially wet peel strength. On the other hand, acrylic solution-type products have a different structure than emulsions, which helps improve the stability of PVDF slurry and, to some extent, enhances the adhesion of the coating to the separator. However, commercially available acrylic solution-type products do not adequately improve the hot-press peel strength of the electrodes, and the permeability of the coated separator is generally poor. To address these issues, the industry has attempted to physically blend emulsion-type and solution-type dispersants, hoping to achieve a balance between high peel strength and low permeability. However, due to the weak interaction and insufficient compatibility between the two types of binders, the actual results are not ideal: the emulsion failed to effectively suppress the weakening of permeability, and the coating state of the solution on PVDF was not improved. Therefore, existing water-based binders struggle to achieve both high peel strength and low permeability, which significantly limits further breakthroughs in lithium-ion battery performance. Summary of the Invention
[0004] To address the problem that existing water-based binders struggle to balance high peel strength and low permeability, this invention provides a method for preparing PVDF dispersion. This method employs a two-stage polymerization process, resulting in PVDF dispersion that significantly improves the dry and wet peel strength between the separator and the electrode, enhances the compactness of the battery cell, and has minimal impact on the separator's permeability. This solves the problem of existing water-based binders struggling to balance high peel strength and low permeability.
[0005] The technical solution adopted by this invention to solve its technical problem is: A method for preparing a PVDF dispersion includes the following steps: S1: Soap-free emulsion polymerization was carried out using acrylic monomers, acrylonitrile, and acrylamide as raw materials to prepare a dispersion emulsion; S2: Using the aforementioned dispersion emulsion, unsaturated carboxylic acid, unsaturated lipophilic monomer, unsaturated hydrophilic monomer, polymer auxiliaries, and water as raw materials, solution polymerization is carried out to obtain an aqueous acrylic copolymer liquid. S3: Adjust the pH of the aqueous acrylic copolymer solution to 5-9 to obtain PVDF dispersion.
[0006] Optionally, step S2 includes: S21: According to the formula amount, the unsaturated carboxylic acid, the unsaturated lipophilic monomer, the unsaturated hydrophilic monomer, the polymeric auxiliary agent and water are mixed to obtain a liquid component; S22: Dissolve the initiator in water to obtain an initiator solution; S23: Under an inert atmosphere, the dispersion emulsion is heated to 60-80°C, and the initiator solution is added to react with the liquid component to obtain an aqueous acrylic copolymer liquid.
[0007] Optionally, based on parts by weight, the amount of acrylic monomer added in step S1 is 15-30.0 parts; the amount of acrylonitrile added is 55-75.0 parts; and the amount of acrylamide added is 5-20.0 parts.
[0008] Optionally, the unsaturated carboxylic acid is selected from at least one of acrylic acid, methacrylic acid, β-carboxyethyl acrylate, itaconic acid, fumaric acid, and maleic acid.
[0009] Optionally, the unsaturated lipophilic monomer is selected from at least one of acrylonitrile, methacrylonitrile, methyl acrylate, methyl methacrylate, ethyl acrylate, and ethyl methacrylate.
[0010] Optionally, the unsaturated hydrophilic monomer is selected from at least one of acrylamide, methacrylamide, N-hydroxyethylacrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, sodium vinyl sulfonate, sodium p-styrene sulfonate, sodium allyl phenyl sulfonate, 2-acrylamido-2-methylpropylphosphonic acid, vinylphosphonic acid, allyl polyoxyethylene ether phosphate, and 2-hydroxyethyl methacrylate phosphate.
[0011] Optionally, the polymeric additive is selected from at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, hydroxymethyl cellulose, polyethylene glycol, polyvinyl alcohol, and polyvinylpyrrolidone.
[0012] Optionally, based on weight parts, the amount of unsaturated carboxylic acid added in step S2 is 10-35.0 parts; the amount of unsaturated lipophilic monomer added is 15-50.0 parts; the amount of unsaturated hydrophilic monomer added is 10-500 parts; and the amount of polymeric auxiliaries added is 5-25 parts.
[0013] Optionally, the initiator in step S22 is selected from at least one of persulfate initiators, hydroperoxide initiators, organic peroxide initiators, and redox initiators.
[0014] Another object of the present invention is to provide a PVDF dispersion prepared by the PVDF dispersion preparation method described above.
[0015] The beneficial effects of this invention are: The PVDF dispersion preparation method provided by this invention employs a two-stage polymerization process of emulsion polymerization and solution polymerization. This allows the prepared water-based modified acrylic copolymer to organically combine the dispersion emulsion and acrylic solution through strong interactions (hydrogen bonds and covalent bonds). The emulsion portion effectively inhibits the weakening of the membrane's permeability due to the coating. In the acrylic solution portion, the acrylate monomers exist in an extended chain state, which enhances the dispersion ability of the dispersion for PVDF. This also improves the coating state of PVDF. After coating, PVDF adheres to the membrane surface in a semi-encapsulated state. This structure can fully utilize the hot-press peel strength of PVDF, solving the problem of excessively low hot-press peel strength between conventional membranes and electrodes. At the same time, the coating layer has little impact on the membrane's permeability, significantly improving the problems of excessively rapid cycle decay and internal short-circuit risk caused by the membrane. Attached Figure Description
[0016] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0017] Figure 1 This is a schematic diagram of the synthesis process of the PVDF dispersion in this invention; Figure 2 These are SEM images of the PVDF membranes coated with PVDF dispersion adhesive in Embodiment 1 and Comparative Example 4 of the present invention. Figure 3 These are digital photographs of the coated diaphragms prepared using PVDF dispersions in Example 1 and Comparative Example 4 of this invention. Figure 4 The hot-pressing peel strength between the PVDF-coated separator and the positive electrode prepared in Example 1 of this invention; Figure 5 This refers to the hot-pressing peel strength between the PVDF-coated separator and the positive electrode prepared in Comparative Example 4 of this invention. Detailed Implementation
[0018] The present invention will now be described in further detail. The embodiments described below are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0019] To address the challenge of existing water-based adhesives simultaneously achieving high peel strength and low permeability, this invention provides a method for preparing PVDF dispersions, comprising the following steps: S1: A soap-free emulsion polymerization was carried out using (meth)acrylic acid, acrylonitrile, and acrylamide as raw materials to prepare a dispersion emulsion; Specifically, this step can be performed as follows: S11: According to the formula, add acrylic monomers, acrylonitrile, acrylamide, part of the neutralizing agent and water into the reaction vessel and stir to mix to obtain the mixed components; The acrylic monomers of this invention are preferably selected from at least one of acrylic acid and methacrylic acid; In this step, acrylic monomers maintain the stability of the dispersion emulsion and PVDF slurry, acrylonitrile provides the dispersion ability of PVDF and keeps it in the state of emulsion droplets, acrylamide helps to improve the bonding strength, and through the synergistic effect of the three, the dispersion of PVDF can be aided and the impact on the air permeability of the membrane can be reduced.
[0020] S12: Dissolve the initiator in water according to the formula to prepare an initiator solution; Preferably, the initiator in this step is selected from at least one of persulfate initiators, hydroperoxide initiators, organic peroxide initiators, and redox initiators; and preferably, 0.1 to 10.0 parts by weight of the initiator are dissolved in pure water to prepare an initiator solution of 0.1 to 10.0 wt.%. S13: After purging nitrogen to remove oxygen from the reactor, slowly heat the mixed components in the reactor to 50-80°C, then slowly add the initiator solution dropwise into the reactor to initiate polymerization. Keep the reaction temperature within the preset range. After all the initiator solution has been added to the reactor, keep it at the temperature for 30-600 minutes to obtain an acrylic copolymer dispersion solution. S14: Add the remaining neutralizing agent and adjust the pH to 5-9 to obtain a dispersion emulsion with a solid content of 5-30.0 wt.%; Preferably, the neutralizing agent in steps S11 and S14 is an inorganic base, and preferably, the neutralizing agent is selected from at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, and ammonia water.
[0021] S2: Solution polymerization is carried out using dispersion emulsion, unsaturated carboxylic acid, unsaturated lipophilic monomer, unsaturated hydrophilic monomer, polymer auxiliaries and water as raw materials to obtain waterborne acrylic copolymer liquid; In this step, PVDF is dispersed with the aid of dispersion emulsion to reduce its impact on the membrane permeability; good adhesive stability is achieved and electrolyte swelling is reduced with unsaturated carboxylic acids; the dispersion and binding force of PVDF is enhanced with unsaturated lipophilic monomers; the adhesion strength to the membrane substrate is enhanced with the aid of unsaturated hydrophilic monomers; and the processing performance is improved with polymeric additives. Through the synergistic effect of the components, ultra-high hot-press peel strength is provided while meeting processing requirements and reducing the impact on the membrane permeability.
[0022] S3: Adjust the pH of the aqueous acrylic copolymer solution to 5-9 to obtain the PVDF dispersion. Preferably, a neutralizing agent is added in this step to adjust the pH to 5-9, thereby obtaining a PVDF dispersion with ultra-high hot-pressing adhesion of 5-30.0 wt.% solid content; Preferably, the neutralizing agent in this step is an inorganic base, and more preferably, the neutralizing agent is selected from at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, and ammonia water.
[0023] See the schematic diagram of the synthesis process of this PVDF dispersion. Figure 1 As shown, (A) is the dispersion emulsion obtained by the first stage of soap-free emulsion polymerization, and (B) is the PVDF dispersion obtained by the two-stage polymerization. There is a strong interaction (hydrogen bond and covalent bond) between the polymer chains after solution polymerization and the dispersion particles.
[0024] To address the safety risks arising from insufficient thermal adhesion between the separator and electrode during lithium battery iteration, this invention proposes a PVDF dispersion with ultra-high thermo-pressurized adhesion and its preparation method. The main component is an aqueous modified acrylic copolymer, prepared via a two-stage polymerization process with a specific design. The first stage polymerization of the aqueous modified acrylic copolymer involves soap-free emulsion polymerization of (meth)acrylic acid, acrylonitrile, acrylamide, an initiator, and a pH adjuster. The second stage polymerization involves solution polymerization of unsaturated carboxylic acids, unsaturated lipophilic monomers, unsaturated hydrophilic monomers, polymer additives, an initiator, and a pH adjuster. This ultra-high thermo-pressurized adhesion PVDF dispersion significantly improves the dry and wet peel strength between the separator and electrode in current lithium battery coating separator systems, enhancing cell compactness while minimizing impact on separator permeability. This improves battery cycle performance, effectively prevents interfacial displacement during charging and discharging, reduces the risk of internal short circuits, and comprehensively enhances battery safety.
[0025] The PVDF dispersion preparation method provided by this invention employs a two-stage polymerization process of emulsion polymerization and solution polymerization. This allows the prepared water-based modified acrylic copolymer to organically combine the dispersion emulsion and acrylic solution through strong interactions (hydrogen bonds and covalent bonds). The emulsion portion effectively inhibits the weakening of the membrane's permeability due to the coating. In the acrylic solution portion, the acrylate monomers exist in an extended chain state, which enhances the dispersion ability of the dispersion for PVDF. This also improves the coating state of PVDF. After coating, PVDF adheres to the membrane surface in a semi-encapsulated state. This structure can fully utilize the hot-press peel strength of PVDF, solving the problem of excessively low hot-press peel strength between conventional membranes and electrodes. At the same time, the coating layer has little impact on the membrane's permeability, significantly improving the problems of excessively rapid cycle decay and internal short-circuit risk caused by the membrane.
[0026] The PVDF dispersant provided by this invention has excellent dispersion and stabilization capabilities for PVDF. The introduction of polymeric additives not only helps stabilize the slurry but also eliminates the need for additional dispersing and wetting agents. PVDF slurries that meet the requirements can be prepared using existing homogenization processes.
[0027] Specifically, the preferred step S2 of the present invention includes: S21: According to the formula amount, unsaturated carboxylic acid, unsaturated lipophilic monomer, unsaturated hydrophilic monomer, polymeric auxiliaries and water are mixed to obtain liquid components; In this preferred step, according to the formula amount, unsaturated carboxylic acid, unsaturated lipophilic monomer, unsaturated hydrophilic monomer, polymeric auxiliaries and pure water are added to a premixing tank and stirred to obtain a homogeneous liquid component for later use; preferably, the monomer concentration in the liquid component is 10-30 wt.
[0028] S22: Dissolve the initiator in water to obtain an initiator solution; Preferably, the initiator in this step is selected from at least one of persulfate initiators, hydroperoxide initiators, organic peroxide initiators, and redox initiators; and preferably, 0.1 to 10.0 parts by weight of the initiator are dissolved in pure water to prepare an initiator solution of 0.1 to 10.0 wt.%.
[0029] S23: Under an inert atmosphere, the dispersion emulsion is heated to 60-80℃, and an initiator solution is added to react with the liquid component to obtain an aqueous acrylic copolymer solution; Preferably, in this step, the dispersion emulsion obtained from soap-free emulsion polymerization in step S1 is added to the reactor, an inert gas is introduced to remove oxygen, stirring is started, and the dispersion emulsion in the reactor is slowly heated to 60-80°C. Then, the initiator solution and the liquid components in the premixing vessel are slowly added to the reactor while reacting, keeping the reaction temperature within the preset range. After all components have been added to the reactor, the mixture is kept at this temperature for 30-600 minutes to obtain the water-based acrylic copolymer solution.
[0030] Preferably, in step S1, the amount of acrylic monomer added is 15-30.0 parts by weight; the amount of acrylonitrile added is 55-75.0 parts; the amount of acrylamide added is 5-20.0 parts; and preferably, the combined amount of neutralizing agent added in steps S11 and S14 is 1-30.0 parts.
[0031] In this invention, the unsaturated carboxylic acid in step S2 is preferably selected from at least one of acrylic acid, methacrylic acid, β-carboxyethyl acrylate, itaconic acid, fumaric acid, and maleic acid; the unsaturated lipophilic monomer is preferably selected from at least one of acrylonitrile, methacrylonitrile, methyl acrylate, methyl methacrylate, ethyl acrylate, and ethyl methacrylate; the unsaturated hydrophilic monomer is preferably selected from at least one of acrylamide, methacrylamide, N-hydroxyethyl acrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, sodium vinyl sulfonate, sodium p-styrene sulfonate, sodium allyl phenyl sulfonate, 2-acrylamido-2-methylpropylphosphonic acid, vinylphosphonic acid, allyl polyoxyethylene ether phosphate, and 2-hydroxyethyl methacrylate phosphate; the polymeric auxiliary agent is preferably selected from at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, hydroxymethyl cellulose, polyethylene glycol, polyvinyl alcohol, and polyvinylpyrrolidone.
[0032] Preferably, in step S2, the amount of unsaturated carboxylic acid added is 10-35.0 parts by weight; the amount of unsaturated lipophilic monomer added is 15-50.0 parts; the amount of unsaturated hydrophilic monomer added is 10-500 parts; and the amount of polymeric auxiliaries added is 5-25 parts.
[0033] In the preferred embodiment of the present invention, the initiator in step S22 is selected from at least one of persulfate initiators, hydroperoxide initiators, organic peroxide initiators, and redox initiators.
[0034] Another object of the present invention is to provide a PVDF dispersion prepared by the PVDF dispersion preparation method described above.
[0035] The PVDF dispersion provided by this invention exhibits excellent electrode hot-pressing peeling force while having minimal impact on the separator's permeability. This PVDF dispersion possesses excellent electrochemical and chemical stability, exhibits less electrolyte swelling, and does not generate small molecule components that affect performance during lithium battery cycling, making it particularly suitable for long-life lithium battery systems. Furthermore, this PVDF dispersion is a water-based product, making it environmentally friendly and cost-effective.
[0036] The PVDF slurry for separators prepared by the PVDF dispersion with ultra-high hot-pressing adhesion provided by this invention can give the separator excellent electrode hot-pressing peel force, while having little impact on the separator's air permeability. This effectively solves the problems of excessively rapid cycle decay and internal short circuit risk caused by low wet peel force between the electrode and the separator, and helps to further improve the safety of lithium batteries.
[0037] In summary, given the urgent need for a solution that combines low permeability enhancement with high electrode peeling force in the niche field of lithium battery separator coating modification, this invention develops a PVDF dispersion product with stable electrochemical performance, which can effectively improve the hot-press peeling force between the separator and the electrode and improve the permeability of the coated separator. This avoids interface displacement during charging and discharging, reduces the risk of internal short circuits, comprehensively improves battery safety, and promotes the industry towards a more efficient and reliable direction.
[0038] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0039] Example 1 This embodiment provides a method for preparing PVDF dispersion, which includes the following steps: First stage of soap-free emulsion polymerization: S01: By weight, 25.0 parts of methacrylic acid, 65.0 parts of acrylonitrile, 10.0 parts of acrylamide, 3.0 parts of sodium hydroxide and pure water are added to the reaction vessel and stirred to obtain a homogeneous mixture with a monomer concentration of 25 wt.%. S02. Dissolve 0.5 parts of ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S03. After purging nitrogen to remove oxygen from the reactor, slowly heat the mixed components in the reactor to 70°C, and then slowly add the initiator solution dropwise to the reactor to initiate polymerization. Maintain the reaction temperature at 70°C. After all the initiator has been added to the reactor, keep it at the temperature for 300 minutes to obtain an acrylic copolymer dispersion solution. S04. Add 8.2 parts of sodium hydroxide and adjust the pH to 7.1 to obtain a dispersion emulsion with a solid content of 20.0 wt.%.
[0040] Second-stage solution polymerization: S05. Add 20.0 parts of acrylic acid, 30.0 parts of acrylonitrile, 10.0 parts of methyl methacrylate, 15.0 parts of acrylamide, 15.0 parts of hydroxyethyl acrylate, 10.0 parts of polyvinyl alcohol and pure water together into a premixing tank and stir to mix, so as to obtain a homogeneous liquid component with a monomer concentration of 20 wt.%, which is ready for use. S06. Dissolve 1.0 part of ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S07. Add the dispersion emulsion obtained from the first stage of soap-free emulsion polymerization to the reactor, purge with nitrogen to remove oxygen, start stirring, and slowly heat the liquid component in the reactor to 70°C. Then, slowly add the initiator solution and the liquid component in the premixing vessel to the reactor while reacting, maintaining the reaction temperature at 70°C. After all components have been added to the reactor, keep it at this temperature for 150 minutes to obtain the water-based acrylic copolymer solution. S08. Add 12.0 parts of sodium hydroxide and adjust the pH to 7.7 to obtain a PVDF dispersion with ultra-high hot-pressing adhesion and a solid content of 15.0 wt.%.
[0041] Example 2 This embodiment provides a method for preparing PVDF dispersion, which includes the following steps: The first stage of soap-free emulsion polymerization is the same as in Example 1: S01. According to the weight parts, 25.0 parts of methacrylic acid, 65.0 parts of acrylonitrile, 10.0 parts of acrylamide, 3.0 parts of sodium hydroxide and pure water are added to the reaction vessel and stirred to obtain a homogeneous mixture with a monomer concentration of 25 wt.%. S02. Dissolve 0.5 parts of ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S03. After purging nitrogen to remove oxygen from the reactor, slowly heat the mixed components in the reactor to 70°C, and then slowly add the initiator solution dropwise to the reactor to initiate polymerization. Maintain the reaction temperature at 70°C. After all the initiator solution has been added to the reactor, keep it at the temperature for 300 minutes to obtain the acrylic copolymer dispersion solution. S04. Add 8.2 parts of sodium hydroxide and adjust the pH to 7.1 to obtain a dispersion emulsion with a solid content of 20.0 wt.%.
[0042] Second-stage solution polymerization: S05. Add 25.0 parts of acrylic acid, 30.0 parts of acrylonitrile, 5.0 parts of ethyl acrylate, 10.0 parts of acrylamide, 15.0 parts of hydroxypropyl acrylate, 15.0 parts of polyvinylpyrrolidone and pure water together into a premixing vessel and stir to mix, so as to obtain a homogeneous liquid component with a monomer concentration of 18 wt.%, which is ready for use. S06. Dissolve 2.0 parts of ammonium persulfate in pure water to prepare a 2.0 wt.% initiator solution; S07. Add the dispersion emulsion obtained from the first stage of soap-free emulsion polymerization to the reactor, purge with nitrogen to remove oxygen, start stirring, and slowly heat the liquid component in the reactor to 75°C. Then, slowly add the initiator solution and the liquid component in the premixing vessel to the reactor while reacting, keeping the reaction temperature at 75°C. After all components have been added to the reactor, keep it at this temperature for 120 minutes to obtain the water-based acrylic copolymer solution. S08. Add 13.5 parts of sodium hydroxide and adjust the pH to 6.9 to obtain a PVDF dispersion with ultra-high hot-pressing adhesion and a solid content of 18.0 wt.%.
[0043] Example 3 This embodiment provides a method for preparing PVDF dispersion, which includes the following steps: First stage of soap-free emulsion polymerization: S01. According to the weight parts, 30.0 parts of acrylic acid, 65.0 parts of acrylonitrile, 5.0 parts of acrylamide, 5.0 parts of lithium hydroxide and pure water are added to the reaction vessel and stirred to obtain a homogeneous mixture with a monomer concentration of 20 wt.%. S02. Dissolve 1.2 parts of potassium persulfate in pure water to prepare a 1.5 wt.% initiator solution; S03. After purging nitrogen to remove oxygen from the reactor, slowly heat the mixed components in the reactor to 65°C, and then slowly add the initiator solution dropwise to the reactor to initiate polymerization. Maintain the reaction temperature at 65°C. After all the initiator solution has been added to the reactor, keep it at the temperature for 240 minutes to obtain the acrylic copolymer dispersion solution. S04. Add 10.0 parts of sodium hydroxide and adjust the pH to 6.4 to obtain a dispersion emulsion with a solid content of 18.0 wt.%.
[0044] Second-stage solution polymerization: S05. Add 35.0 parts itaconic acid, 35.0 parts acrylonitrile, 15.0 parts methyl acrylate, 10.0 parts acrylamide, 5.0 parts sodium carboxymethyl cellulose and pure water together into a premixing vessel and stir to obtain a homogeneous liquid component with a monomer concentration of 16 wt.%, which is ready for use. S06. Dissolve 1.5 parts of potassium persulfate in pure water to prepare a 1.5 wt.% initiator solution; S07. Add the dispersion emulsion obtained from the first stage of soap-free emulsion polymerization to the reactor, purge with nitrogen to remove oxygen, start stirring, and slowly heat the liquid component in the reactor to 65°C. Then, slowly add the initiator solution and the liquid component in the premixing vessel to the reactor while reacting, maintaining the reaction temperature at 65°C. After all components have been added to the reactor, keep it at this temperature for 210 minutes to obtain the water-based acrylic copolymer solution. S08. Add 20.5 parts of lithium hydroxide and adjust the pH to 6.6 to obtain a PVDF dispersion with ultra-high hot-pressing adhesion and a solid content of 12.0 wt.%.
[0045] Example 4 This embodiment provides a method for preparing PVDF dispersion, which includes the following steps: First stage of soap-free emulsion polymerization: S01. According to the weight parts, 15.0 parts of acrylic acid, 75.0 parts of acrylonitrile, 10.0 parts of acrylamide, 4.0 parts of calcium hydroxide and pure water are added to the reaction vessel and stirred to obtain a homogeneous mixture with a monomer concentration of 15 wt.%. S02. Dissolve 1.2 parts of sodium persulfate in pure water to prepare a 1.5 wt.% initiator solution; S03. After purging nitrogen to remove oxygen from the reactor, slowly heat the mixed components in the reactor to 72°C, and then slowly add the initiator solution dropwise into the reactor to initiate polymerization. Maintain the reaction temperature at 72°C. After all the initiator solution has been added to the reactor, keep it at the temperature for 270 minutes to obtain the acrylic copolymer dispersion solution. S04, add 4.0 parts of calcium hydroxide, adjust the pH to 6.4, and obtain a dispersion emulsion with a solid content of 18.0 wt.%.
[0046] Second-stage solution polymerization: S05. Add 5.0 parts of methacrylic acid, 5.0 parts of acrylic acid, 15.0 parts of acrylonitrile, 20.0 parts of acrylamide, 25.0 parts of 2-acrylamido-2-methylpropanesulfonic acid, 10.0 parts of 2-hydroxyethyl methacrylate phosphate, 20.0 parts of hydroxymethyl cellulose and pure water to a premixing vessel and stir to obtain a homogeneous liquid component with a monomer concentration of 15 wt.%, which is then ready for use. S06. Dissolve 2.5 parts of sodium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S07. Add the dispersion emulsion obtained from the first stage of soap-free emulsion polymerization to the reactor, purge with nitrogen to remove oxygen, start stirring, and slowly heat the liquid component in the reactor to 72°C. Then, slowly add the initiator solution and the liquid component in the premixing vessel to the reactor while reacting, maintaining the reaction temperature at 72°C. After all components have been added to the reactor, keep it at this temperature for 180 minutes to obtain the water-based acrylic copolymer solution. S08. Add 15.0 parts of calcium hydroxide and adjust the pH to 7.2 to obtain a PVDF dispersion with ultra-high hot-pressing adhesion and a solid content of 10.0 wt.%.
[0047] Example 5 This embodiment provides a method for preparing PVDF dispersion, which includes the following steps: First stage of soap-free emulsion polymerization: S01. According to the weight parts, 20.0 parts of acrylic acid, 60.0 parts of acrylonitrile, 20.0 parts of acrylamide, 6.0 parts of ammonia water and pure water are added to the reaction vessel and stirred and mixed to obtain a homogeneous mixed component with a monomer concentration of 25 wt.%. S02. Dissolve 1.5 parts of ammonium persulfate and 1 part of sodium sulfite in pure water to prepare a 1.5 wt.% initiator solution; S03. After purging nitrogen to remove oxygen from the reactor, slowly heat the mixed components in the reactor to 75°C, and then slowly add the initiator solution dropwise to the reactor to initiate polymerization. Maintain the reaction temperature at 75°C. After all the initiator solution has been added to the reactor, keep it at the temperature for 200 minutes to obtain the acrylic copolymer dispersion solution. S04. Add 11.0 parts of ammonia water and adjust the pH to 6.4 to obtain a dispersion emulsion with a solid content of 20.0 wt.%.
[0048] Second-stage solution polymerization: S05. Add 15.0 parts of acrylic acid, 5.0 parts of methacrylic acid, 5.0 parts of β-carboxyethyl acrylate, 40.0 parts of acrylonitrile, 15.0 parts of acrylamide, 10.0 parts of sodium vinyl sulfonate, 10.0 parts of polyethylene glycol and pure water to a premixing vessel and stir to obtain a homogeneous liquid component with a monomer concentration of 25 wt.%, which is ready for use. S06. Dissolve 2.0 parts of ammonium persulfate and sodium sulfite in pure water to prepare a 1.0 wt.% initiator solution; S07. Add the dispersion emulsion obtained from the first stage of soap-free emulsion polymerization to the reactor, purge with nitrogen to remove oxygen, start stirring, and slowly heat the liquid component in the reactor to 75°C. Then, slowly add the initiator solution and the liquid component in the premixing vessel to the reactor while reacting, keeping the reaction temperature at 75°C. After all components have been added to the reactor, keep it at this temperature for 150 minutes to obtain the water-based acrylic copolymer solution. S08. Add 16.5 parts of ammonia water and adjust the pH to 7.2 to obtain a PVDF dispersion with ultra-high hot-pressing adhesion and a solid content of 20.0 wt.%.
[0049] Example 6 This embodiment provides a method for preparing PVDF dispersion, which includes the following steps: First stage of soap-free emulsion polymerization: S01. According to the weight parts, 25.0 parts of acrylic acid, 65.0 parts of acrylonitrile, 10.0 parts of acrylamide, 4.0 parts of lithium hydroxide and pure water are added to the reaction vessel and stirred and mixed to obtain a homogeneous mixed component with a monomer concentration of 20 wt.%. S02. Dissolve 0.9 parts of ammonium persulfate and 0.9 parts of ascorbic acid in pure water to prepare 1.0 wt.% initiator solutions respectively; S03. After purging nitrogen to remove oxygen from the reactor, slowly heat the mixed components in the reactor to 70°C, and then slowly add the initiator solution dropwise into the reactor to initiate polymerization. Maintain the reaction temperature at 70°C. After all the initiator solution has been added to the reactor, keep it at the temperature for 210 minutes to obtain the acrylic copolymer dispersion solution. S04, add 9.0 parts of lithium hydroxide, adjust the pH to 6.4, and obtain a dispersion emulsion with a solid content of 18.0 wt.%.
[0050] Second-stage solution polymerization: S05. Add 15.0 parts of acrylic acid, 5.0 parts of methacrylic acid, 40.0 parts of acrylonitrile, 5.0 parts of methyl methacrylate, 10.0 parts of acrylamide, 15.0 parts of hydroxypropyl acrylate, 10.0 parts of polyvinylpyrrolidone and pure water to a premixing vessel and stir to mix, so as to obtain a homogeneous liquid component with a monomer concentration of 18 wt.%, which is ready for use. S06. Dissolve 0.8 parts of ammonium persulfate and 0.8 parts of ascorbic acid in pure water to prepare 1.2 wt.% initiator solutions respectively; S07. Add the dispersion emulsion obtained from the first stage of soap-free emulsion polymerization to the reactor, purge with nitrogen to remove oxygen, start stirring, and slowly heat the liquid component in the reactor to 70°C. Then, slowly add the initiator solution and the liquid component in the premixing vessel to the reactor while reacting, maintaining the reaction temperature at 70°C. After all components have been added to the reactor, keep it at this temperature for 300 minutes to obtain the water-based acrylic copolymer solution. S08. Add 10.5 parts of lithium hydroxide and adjust the pH to 6.9 to obtain a PVDF dispersion with ultra-high hot-pressing adhesion and a solid content of 16.0 wt.%.
[0051] Comparative Example 1 This comparative example provides a method for preparing PVDF dispersion, which includes the following steps: S01: By weight, 25.0 parts of methacrylic acid, 65.0 parts of acrylonitrile, 10.0 parts of acrylamide, 3.0 parts of sodium hydroxide and pure water are added to the reaction vessel and stirred to obtain a homogeneous mixture with a monomer concentration of 25 wt.%. S02. Dissolve 0.5 parts of ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S03. After purging nitrogen to remove oxygen from the reactor, slowly heat the mixed components in the reactor to 70°C, and then slowly add the initiator solution dropwise to the reactor to initiate polymerization. Maintain the reaction temperature at 70°C. After all the initiator has been added to the reactor, keep it at the temperature for 300 minutes to obtain an acrylic copolymer dispersion solution. S04. Add 8.2 parts of sodium hydroxide to adjust the pH to 7.1 to obtain a dispersion emulsion with a solid content of 20.0 wt.%, i.e., PVDF dispersion gel.
[0052] The difference between this comparative example and Example 1 is that the second-stage solution polymerization was not performed.
[0053] Comparative Example 2 This comparative example provides a method for preparing PVDF dispersion, which includes the following steps: S01. According to the weight parts, 20.0 parts of acrylic acid, 30.0 parts of acrylonitrile, 10.0 parts of methyl methacrylate, 15.0 parts of acrylamide, 15.0 parts of hydroxyethyl acrylate, 10.0 parts of polyvinyl alcohol and pure water are added to a premixing tank and stirred to obtain a homogeneous liquid component with a monomer concentration of 20 wt.%, which is ready for use. S02. Dissolve 1.0 part of ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S03. Add 100.0 parts of pure water to the reactor, purge with nitrogen to remove oxygen, start stirring, and slowly heat the liquid components in the reactor to 70°C. Then, slowly add the initiator solution and the liquid components in the premixing vessel to the reactor while they are reacting, keeping the reaction temperature at 70°C. After all components have been added to the reactor, keep it at this temperature for 150 minutes to obtain the water-based acrylic copolymer solution. S04. Add 12.0 parts of sodium hydroxide to adjust the pH to 7.7 to obtain PVDF dispersion.
[0054] The difference between this comparative example and Example 1 is that the first stage of soap-free emulsion polymerization was not performed, and pure water was used instead of the dispersion emulsion in Example 1 for solution polymerization.
[0055] Comparative Example 3 This comparative example provides a method for preparing PVDF dispersion, which includes the following steps: First stage of soap-free emulsion polymerization: S01. According to the weight parts, 30.0 parts of acrylic acid, 65.0 parts of acrylonitrile, 5.0 parts of acrylamide, 5.0 parts of lithium hydroxide and pure water are added to the reaction vessel and stirred to obtain a homogeneous mixture with a monomer concentration of 20 wt.%. S02. Dissolve 1.2 parts of potassium persulfate in pure water to prepare a 1.5 wt.% initiator solution; S03. After purging nitrogen to remove oxygen from the reactor, slowly heat the mixed components in the reactor to 65°C, and then slowly add the initiator solution dropwise to the reactor to initiate polymerization. Maintain the reaction temperature at 65°C. After all the initiator solution has been added to the reactor, keep it at the temperature for 240 minutes to obtain the acrylic copolymer dispersion solution. S04. Add 10.0 parts of sodium hydroxide and adjust the pH to 6.4 to obtain a dispersion emulsion with a solid content of 18.0 wt.%.
[0056] Second-stage solution polymerization: S05. Add 35.0 parts itaconic acid, 35.0 parts acrylonitrile, 15.0 parts methyl acrylate, 10.0 parts acrylamide, 5.0 parts sodium carboxymethyl cellulose and pure water together into a premixing vessel and stir to obtain a homogeneous liquid component with a monomer concentration of 16 wt.%, which is ready for use. S06. Dissolve 1.5 parts of potassium persulfate in pure water to prepare a 1.5 wt.% initiator solution; S07. Add 100.0 parts of pure water to the reactor, purge with nitrogen to remove oxygen, start stirring, and slowly heat the liquid components in the reactor to 65°C. Then, while reacting, slowly add the initiator solution and the liquid components in the premixing vessel to the reactor, maintaining the reaction temperature at 65°C. After all components have been added to the reactor, keep it at this temperature for 210 minutes to obtain the water-based acrylic copolymer solution. S08. Add 20.5 parts of lithium hydroxide and adjust the pH to 6.6 to obtain the solution polymerization product; S09: Physically mix the dispersion emulsion with the solution polymerization product to obtain a blended aqueous dispersion, namely PVDF dispersion.
[0057] Compared with Example 3, this comparative example only involves separately performing the first stage of soap-free emulsion polymerization and the second stage of solution polymerization, and then physically mixing the products obtained from the two polymerization stages to obtain a blended aqueous dispersion.
[0058] Comparative Example 4 This comparative example uses a commercially available PVDF dispersion (Indira LA133) for evaluation.
[0059] The dispersant products prepared in the above examples and comparative examples were homogenized using a disperser. The dry weight of the product was mixed with PVDF at a mass ratio of 1:10. After high-speed dispersion for 4 hours, a PVDF dispersion slurry was obtained. The PVDF dispersion slurry was then coated onto a PE membrane. After drying, a coated membrane with a thickness of about 2 micrometers was obtained, and its air permeability was tested. The membrane was then hot-pressed with the positive electrode sheet, and its peel strength before and after immersion in electrolyte was tested. The peel strength between the diaphragm and the positive electrode sheet was tested by peeling with 20mm tape at a 90-degree angle; the greater the peel strength, the better. Wet peel strength was tested by immersing the hot-pressed sample in an electrolyte solvent with a mass ratio of EC:DEC:DMC = 1:1:1 and holding it at 60°C for 2 hours. The air permeability of the coated diaphragm is tested using an air permeability meter, and the difference is compared by the increase in air permeability; the lower the value, the better.
[0060] See Figure 2 , Figure 3 As shown, the PVDF particles prepared in Example 1 of this invention are only partially coated with the dispersant, which can fully exert the hot-pressing peeling force performance; the coating state of Comparative Example 4 is fully coated.
[0061] See Figure 4 , Figure 5 As shown, the PVDF-coated separator prepared in Example 1 of the present invention exhibits a 260% increase in peel strength with respect to the positive electrode during hot pressing compared to Comparative Example 4.
[0062] The test results are shown in Table 1: Table 1 As can be seen from the data in the table above, the PVDF slurry for diaphragms prepared by the PVDF dispersant provided in the various embodiments of the present invention can impart excellent electrode hot-pressing peeling force to the diaphragm, while having little impact on the air permeability of the diaphragm.
[0063] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A method for preparing a PVDF dispersion, characterized in that, Includes the following steps: S1: Soap-free emulsion polymerization was carried out using acrylic monomers, acrylonitrile, and acrylamide as raw materials to prepare a dispersion emulsion; S2: Using the aforementioned dispersion emulsion, unsaturated carboxylic acid, unsaturated lipophilic monomer, unsaturated hydrophilic monomer, polymer auxiliaries, and water as raw materials, solution polymerization is carried out to obtain an aqueous acrylic copolymer liquid. S3: Adjust the pH of the aqueous acrylic copolymer solution to 5-9 to obtain PVDF dispersion; Based on parts by weight, the amount of acrylic monomer added in step S1 is 15-30.0 parts; the amount of acrylonitrile added is 55-75.0 parts; and the amount of acrylamide added is 5-20.0 parts. Based on weight parts, the amount of unsaturated carboxylic acid added in step S2 is 10-35.0 parts; the amount of unsaturated lipophilic monomer added is 15-50.0 parts; the amount of unsaturated hydrophilic monomer added is 10-500 parts; and the amount of polymeric auxiliaries added is 5-25 parts.
2. The method for preparing PVDF dispersion as described in claim 1, characterized in that, Step S2 includes: S21: According to the formula amount, the unsaturated carboxylic acid, the unsaturated lipophilic monomer, the unsaturated hydrophilic monomer, the polymeric auxiliary agent and water are mixed to obtain a liquid component; S22: Dissolve the initiator in water to obtain an initiator solution; S23: Under an inert atmosphere, the dispersion emulsion is heated to 60-80°C, and the initiator solution is added to react with the liquid component to obtain an aqueous acrylic copolymer liquid.
3. The method for preparing PVDF dispersion as described in claim 1, characterized in that, The unsaturated carboxylic acid is selected from at least one of acrylic acid, methacrylic acid, β-carboxyethyl acrylate, itaconic acid, fumaric acid, and maleic acid.
4. The method for preparing PVDF dispersion as described in claim 1, characterized in that, The unsaturated lipophilic monomer is selected from at least one of acrylonitrile, methacrylonitrile, methyl acrylate, methyl methacrylate, ethyl acrylate, and ethyl methacrylate.
5. The method for preparing PVDF dispersion as described in claim 1, characterized in that, The unsaturated hydrophilic monomer is selected from at least one of acrylamide, methacrylamide, N-hydroxyethylacrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, sodium vinyl sulfonate, sodium p-styrene sulfonate, sodium phenyl sulfonate, 2-acrylamido-2-methylpropylphosphonic acid, vinylphosphonic acid, allyl polyoxyethylene ether phosphate, and 2-hydroxyethyl methacrylate phosphate.
6. The method for preparing PVDF dispersion as described in claim 1, characterized in that, The polymeric additive is selected from at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, hydroxymethyl cellulose, polyethylene glycol, polyvinyl alcohol, and polyvinylpyrrolidone.
7. The method for preparing PVDF dispersion as described in claim 2, characterized in that, The initiator mentioned in step S22 is selected from at least one of persulfate initiators, hydroperoxide initiators, organic peroxide initiators, and redox initiators.
8. A PVDF dispersion, characterized in that, The PVDF dispersion is prepared by the method described in any one of claims 1-7.
Citation Information
Patent Citations
Electrode binder composition for lithium ion power storage device
CN115702173A
Aqueous acrylic copolymer dispersion
JP2010053227A
